A review of electrical burns admitted in a Philippine Tertiary Hospital Burn Center - Margarita S. Elloso; Jose Joven V. Cruz (Elsevier, 2017)
Electrical injury is the 4th most common cause of burn which continues to be one of the most distressing trauma injuries in developing countries. In the Philippines, the number of electrical injuries are typically underreported.This study is a descriptive retrospective analysis of patients suffering from electrical burns admitted at the Philippine General Hospital, Alfredo T. Ramirez Burn Center (PGH-ATR) from January 2004 to December 2012.A total of 706 (28.3%) patients with electrical burns were reviewed. Majority were males of working age and injuries were work related (80.45%) of which 75.5% were construction workers. The primary cause in majority of the cases was accidental contact of overhead electrical power lines by metal poles. Most of the patients admitted were high voltage electrical injuries (79.46%), 46.03% had severe electrical burns and 11.33% had associated traumatic injuries. There was a delay in time of injury to admission, 48.73% arrived at the emergency room >8 h after the injury. 40.73% of the patients underwent surgery, most of which had moderate to severe burns. Average length of stay was 14-28 days. Overall morbidity rate and mortality rate were 2.12% and 2.41% respectively.The increase in the rate of electrical injuries may be linked to the country's rapid pace of industrialization. Prevention must be prioritized and preventive activities should be aimed to reduce the incidence. Keywords: Electrical, Burn, Voltage, Work, Surface, Injury